Diseño de OTAs de baja transconductancia con rango lineal extendido y sus aplicaciones en señales EEG - Campana Valderrama, Franco Renato (2024)
In this work, the design of symmetric OTAs with low transconductance value (nA/V order) and their application in low frequency and low power is presented. For this aim, the series-parallel (S-P) mirrors was used, which divided the differential pair transconductance. With this technique, a 1 nA/V transconductor is reached. Techniques for extend the linear range (hundreds milivolts) of the differential pair will presented too. The Advanced Compact MOSFET Model ACM was used in the design process. These symmetric OTAs designed will be used in active filters with low central frequency, for biomedical applications (EEG signals). The capacitors of this filters are in the picofaradads order, and are off chip. These OTAs and filters were designed in 0.8 um standard technology. These techniques that we will present will be validated through simulation